Field notes contributed by Thomas J. Staudt, summer 1986 - Staudt, Thomas J.et al (1986)
List of birds and locations contributed by Thomas J. Staudt. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of summer 1986. Epson - sheet feed